Groundwater enhances above‐ground growth in mangroves. (4th December 2018) - Hayes, Matthew A.; Jesse, Amber; Welti, Nina; Tabet, Basam; Lockington, David; Lovelock, Catherine E.
Abstract: Groundwater flow through coastal wetlands plays an important role in the maintenance of productivity of intertidal ecosystems. Groundwater can reduce salinity and increase nutrient availability which can enhance plant growth and alter plant biomass allocation patterns. Here, we used stable isotopes of oxygen and hydrogen to assess how groundwater influences below‐ground and above‐ground growth in the widespread mangrove species Avicennia marina . We found source water within tree stems varied seasonally, with non‐saline water use higher in the wet season when rainwater availability was highest compared to the dry season. Stems with higher proportional contribution of non‐saline water had increased above‐ground growth but no effect on below‐ground growth. Below‐ground growth was however influenced by nutrient availability across the intertidal zone which was higher in the high‐ compared to the low‐intertidal zone. Synthesis . This study shows that mangroves use non‐saline groundwater and rainwater when available rather than saline water sources. Groundwater flows into the intertidal stimulates organic matter accumulation in above‐ground biomass suggesting the availability of non‐saline water sources, such as groundwater and rainfall, are important for the growth and productivity of mangrove forests. Abstract : This study shows that mangroves use non‐saline groundwater and rainwater when available rather than saline water sources. Groundwater flows into the intertidal stimulates organic matter accumulation in above‐ground biomass suggesting the availability of non‐saline water sources, such as groundwater and rainfall, are important for the growth and productivity of mangrove forests.